Reality of using electronic activities in educational process from the perspective of schools principals in educational directorate of Ramallah and Al-Bireh - Karzoun, Noor Anees (Journal of Educational and Psychological Sciences, 2023)
This study aimed to find out Reality of using electronic activities in educational process From the perspective of schools principals in educational directorate of ramallah and al-bireh, The study used descriptive approach. The researcher built a questionnaire, and it consisted of (45) paragraphs representing the reality of using electronic activities in three areas: (mechanisms, obstacles, attitudes) the study sample consisted of the (30) school principals. The results of the study showed after statistical analysis that the area of the mechanisms came with an average degree, while the area of attitudes came at a high degree and the area of obstacles came with an average degree, and showed that there are no statistically significant differences according to variables: (gender, the scientific qualification, and years of experience). The researcher made a number of recommendations based on the study’s findings, chief among them the creation of an e-learning infrastructure in remote schools by supplying the computers, networks, and other tools required to reach classrooms and developmental spaces, as well as the improvement of school principals’ favorable attitudes toward electronic activities by encouraging them to put forth initiatives pertaining to the use of electronic activities.